HISTORY OF SUIT (Web of Teachers: Inderscience Research, 2024)
This article explores the rich history of the suit, tracing its evolution from its origins to modern-day interpretations. It delves into the cultural, societal, and fashion influences that have shaped the suit over centuries, analyzing its significance in different eras and regions. The article employs a multidisciplinary approach, drawing from historical records, literature, and fashion studies to provide a comprehensive understanding of the suit's journey through time.